The effect of training with (educational - training) methods in developing the skillful performance of boxers - Ahmed, Saif Saad; Mandeel, Ammar Taher; Abdulhameed, Noor Dheyaa; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The Dissertation seasons five chapters The first chapter seasons: Enclosed on the introduction & the importance of the research which focuses on applying certain things after arranging them in accordance with basic Boxing skills that considered as one of the important sport games tackled by scientific progress movement.That depends on various primary tests which shows the readiness of the sample for educational and training work and in this we can set up a work plan coping with different levels of sample individuals. The problem lies in: There was a randomness in education and training process through following classical unplanned scientific methods which make boxers cease training process. This will lead to waste time and efforts of both the player and the coach. Ultimately , the expected goals set in the curriculum can’t be achieved and this will lead to resentment of the boxers. Research goals: The search at: - Recogmize the effect of(Educational – Training) a system usinig proficient style in prepving beginners boxers startiig fram Education stages till engagement in boxing competition for ages (13-14) year: The researcher assumptions the following: The Educational – Training system morally affects in developing sample performance in eeach research stage The second chapter seasons: -Similar theoretical studies: This chapter includes several aspects, as the meaning of the system and its stages , motive learning , the factors that affect in education process , the goals of motive learning , the notion of proficient education , the work demands in proficient system , the psychological side , the notion of sport training and how to select juniors in boxing and skills setting up( basic positions of boxing) which are readiness stand, feet movements, left & right punches and its defenses . The third chapter seasons: Research systematicness and its field procedures: The researcher used empirical curriculum to solve research problem since it is fit to it. The researcher chose the society of beginners boxers in Al-Rafidaen Sport Club in Al-Qadissiyah province.They were 12 boxers with ages (13-14)years.The researcher conducted his surveillance experiments on a sample of research community who are five of the beginners boxers Through this experiments time is recognized and the assistant team of the main work have been identified to avoid the mistakes and place suitability where work conducted and making sure of devices used. -Presenting , analyzing and discussing results. This chapter includes presenting, analyzing and discussing results to fulfill research goals and hypothesis. The more important recommendations and conclusions: The more important conclusions: After handling results with statistical methods, the researcher deduced the following conclusions: -Educational approach prepared for motive skills has great effect on the process of motive skills learning. -The proficient style has a great role in individuals’ reaching to high level of perfectness .This comes from the role of medial tests used in proficient style. -Training approach has its active role in achieving the principle of developing motion, physical, psychological situation skills for sample individuals. Recommendations: The researcher recommends the following , depending on his results: • The necessity of generalizing this system which prepared by the researcher to develop beginners boxers performance. • The necessity of using principle of proficient style in teaching boxing skills. • The necessity of using standard levels which are concluded by the researcher with the sample’s individuals (juniors( • Paying attention to psychological side(motivation) which has an important effect on continuing performance and diligence in training.